Identifikasi Bakteri Pada Pasien Infeksi Luka Operasi (ILO) Pasca Bedah Orthopedi Di RS X Pekalongan - Siska Aulia Asih; Mulia Susanti (Jurnal Anestesi, 2024)
Surgical wound infection (SSI) is an infection caused by pathogenic microorganisms that contaminate surgical wounds during surgery or after surgery. ILO can occur, among other things, in cases of orthopedic surgery. ILO after orthopedic surgery generally occurs within 30 days after surgery (if not using implants) or within 1 year (if using implants). Based on medical record data from Hospital This research is a descriptive study with the aim of finding out the types of bacteria found in ILO isolates after undergoing orthopedic surgery. Samples were taken using census sampling techniques during March 2023. The total number of samples obtained was 5 samples. The research was carried out by identifying bacterial findings based on biochemical properties. The results of the study showed that from the 5 specimens examined, Staphylococcus aureus bacteria were found with gram positive characteristics, MSA test (+) mannitol fermenter, sensitive to novobiocin, positive catalase, and positive CPT. Other bacteria found were Escherichia coli with gram negative characteristics, lactose fermenting MCA, metallic red colonies, and a positive indole test. Achromobacter sp with gram negative characteristics, non-lactose fermenter MCA, positive citrate, and positive oxidase test. It can be concluded that from ILO isolates after orthopedic surgery at Hospital